(untitled) (Eurasian Medical Research Periodical, 2022)
Given their enormous potential in biomedical applications, nanomaterials have seen significant advancement in recent years. Due to their distinctive physicochemical characteristics, carbon nanotubes (CNTs) have gained popularity as a tool for cancer treatment and diagnosis. Breast cancer, the most common type in women, is one of these types of cancer. Breast cancer is extremely dangerous to one’s health. Every year, the prevalence of BC spreads globally. Methods: MCF-7 cell line subcultured in vitro and exposed to different concentration of CNTs for 24 hours. Then measured by MTT test. Results: CNTs significantly inhibited the MCF-7 cell line proliferation after 24 hours particularly in 400 and 500µg/ml of CNTs Conclusion: CNTs have a highly toxicity against cancer cells